An assessment of certain methods of stress-analysis of rectangular multi-web box beams - Griffin, K. H. (College of Aeronautics, Cranfield, 1956)
The stress distribution in an unswept multi-web box under shear load applied at the centre of a rigid tip rib is examined, and compared with results obtained by a method which replaces the shear webs by a shear-carrying continuum. Continues ...